1983
DOI: 10.1111/j.1348-0421.1983.tb00611.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxin Production by Clostridium sordellii Strains

Abstract: A total of 55 strains of Clostridium sordellii, 21 lethal toxin-positive and 34 lethal toxin-negative, were tested for cytotoxin production in brain heart infusion medium supplemented with 0.2% Na2HP04 (m-BHI) and cooked-meat-glucose (CMG) medium using baby hamster kidney (BHK-21jWI-2) cells as indicator cells. The m-BHI medium was preferred to CMG medium and 24 hr of incubation was sufficient for cytotoxin production. Nineteen of the 21 toxigenic strains were also cytotoxigenic, and the strength of the cytoto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
15
0

Year Published

1985
1985
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 17 publications
0
15
0
Order By: Relevance
“…Antisera were prepared by bleeding one week after the final injection. The neutralization test for cytotoxicity was performed by the method described previously (9). The results of the neutralization test on BHK cells are given in Table 1.…”
mentioning
confidence: 99%
“…Antisera were prepared by bleeding one week after the final injection. The neutralization test for cytotoxicity was performed by the method described previously (9). The results of the neutralization test on BHK cells are given in Table 1.…”
mentioning
confidence: 99%
“…37 The toxins of C. sordellii are often compared with toxins A and B of Clostridium difficile, and it has been reported that a specific antiserum against the lethal toxin of C. sordellii successfully neutralized the cytotoxic and lethal activities of C. difficile toxin B. 7,19,26,31,37,47 In this report, we present 8 cases of perinatal mortality in foals associated with navel infection by C. sordellii.…”
mentioning
confidence: 97%
“…Consequently, LT masks the action of HT in culture supernatants, and the differentiation between pathogenic and nonpathogenic C. sordellii strains has been conventionally based on LT production [8]. A consequence of this is that C. sordellii vaccines have been produced on the basis of inducing LT-specific antitoxins alone, however, the lethal activity of HT is not as low as the activities of other clostridial lethal toxins [6,20,21].The toxins of C. sordellii have often been compared with toxin A and toxin B produced by C. difficile [5,12,15,17]. The biological and antigenic properties of toxin A and toxin B are very similar to those of HT and LT [5,12,17,23,24].…”
mentioning
confidence: 99%
“…The toxins of C. sordellii have often been compared with toxin A and toxin B produced by C. difficile [5,12,15,17]. The biological and antigenic properties of toxin A and toxin B are very similar to those of HT and LT [5,12,17,23,24].…”
mentioning
confidence: 99%
See 1 more Smart Citation